Thirteen ways to kill Lulabelle Rock - Woolf, Maud (Angry Robot, 2024)
The 13th copy made of washed-up actress Lulabelle Rock, tasked with tracking down and eliminating her predecessors, finds her mission made difficult by a developing conscience and falling love with one of her targets.